2003
DOI: 10.1016/j.str.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobase Pairing in Expanded Watson-Crick-like Genetic Information Systems

Abstract: To guide the design of alternative genetic systems, we measured melting temperatures of DNA duplexes containing matched and mismatched nucleobase pairs from natural and unnatural structures. The pairs were analyzed in terms of structural features, including nucleobase size, number of hydrogen bonds formed, the presence of uncompensated hydrogen bonding functional groups, the nature of the bond joining the nucleobase to the sugar, and nucleobase charge. The results suggest that stability of nucleobase pairs cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 58 publications
(3 reference statements)
9
128
0
4
Order By: Relevance
“…[13][14][15][17][18][19] The Watson-Crick like iGiC pair, with the amino and carbonyl groups transposed relative to the Watson-Crick GC pair, provides an expanded alphabet [20][21][22][23][24][25][26] for further understanding interactions that shape nucleic acid structure (Figure 1). 7,[25][26][27][28][29][30][31][32] Here, thermodynamic studies of tandem GA pairs flanked by iGiC pairs are reported along with NMR structures of the RNA duplexes (GCiGGAiCGCA) 2 and (GGiCGAiGCCA) 2 . NMR restrained molecular dynamics and energy minimization of (GCiGGAiCGCA) 2 reveal a conformation of tandem sheared GA pairs closed by Watson-Crick like iGiC pairs.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][17][18][19] The Watson-Crick like iGiC pair, with the amino and carbonyl groups transposed relative to the Watson-Crick GC pair, provides an expanded alphabet [20][21][22][23][24][25][26] for further understanding interactions that shape nucleic acid structure (Figure 1). 7,[25][26][27][28][29][30][31][32] Here, thermodynamic studies of tandem GA pairs flanked by iGiC pairs are reported along with NMR structures of the RNA duplexes (GCiGGAiCGCA) 2 and (GGiCGAiGCCA) 2 . NMR restrained molecular dynamics and energy minimization of (GCiGGAiCGCA) 2 reveal a conformation of tandem sheared GA pairs closed by Watson-Crick like iGiC pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The successful incorporation of nonnatural base pairs into nucleic acid duplexes has given ample reason to seriously consider this question (Switzer et al 1989;Piccirilli et al 1990;Geyer et al 2003). Most of the nonnatural base pairs studied thus far have maintained the form of a base comprised of a six-membered ring (like a pyrimidine) paired with a base comprised of fused five-and six-membered rings (like a purine), which can be accommodated in a helix also containing canonical WatsonCrick base pairs.…”
Section: Recent Resultsmentioning
confidence: 99%
“…1−11 Our laboratories have constructed an artificially expanded genetic information system (AEGIS). 10,12 The AEGIS is a species of DNA having additional nucleobases that present alternative hydrogen bonding patterns, allowing its members to form mutually exclusive pairing schemes. Some members of the AEGIS are used in the clinic to monitor the viral load of patients infected with human immunodeficiency virus and hepatitis C virus.…”
mentioning
confidence: 99%